Effects of Icariin and Its Metabolites on GPCR Regulation and MK-801-Induced Schizophrenia-Like Behaviors in Mice - Su Hui Seong; Seo Hyun Kim; Jong Hoon Ryu; Jin-Woo Jeong; Hyun Ah Jung; Jae Sue Choi (Molecules, 2023)
Icariin, a major bioactive compound found in the Epimedium genus, has been reported to exert protective effects against neurodegenerative disorders. In the current study, we aimed to investigate the regulatory effect of icariin and its active metabolites (icariside II and icaritin) against prime G-protein-coupled receptor targets, considering their association with neuronal disorders. Icariside II exhibited selective agonist activity towards the dopamine D3 receptor (D3R), with half-maximal effective concentrations of 13.29 μM. Additionally, they effectively inhibited the specific binding of radioligands to D3R. Molecular docking analysis revealed that icariside II potentially exerts its agonistic effect through hydrogen-bonding interaction with Asp110 of the D3R, accompanied by negative binding energy. Conversely, icaritin demonstrated selective antagonist effects on the muscarinic acetylcholine M2 receptor (M2R). Radioligand binding assay and molecular docking analysis identified icaritin as an orthosteric ligand for M2R. Furthermore, all three compounds, icariin and its two metabolites, successfully mitigated MK-801-induced schizophrenia-like symptoms, including deficits in prepulse inhibition and social interaction, in mice. In summary, these findings highlight the potential of icariin and its metabolites as promising lead structures for the discovery of new drugs targeting cognitive and neurodegenerative disorders.